Transformative Islamic Education in Politics: Political Education of Religious Figures in The 2024 Election - Sahari Sahari; Adri Lundeto; Imam Mash’ud; Reza Adeputra Tohis (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Transformative Islamic education focuses on teaching religious values and shaping critical awareness and social responsibility, including in the political context. This study analyzes transformative Islamic education in political education carried out by Islamic religious figures during the 2024 General Election in North Sulawesi. The research uses a qualitative method with a case study approach. The sample selection employs purposive sampling, involving 23 informants of Islamic religious figures and Muslim communities from 12 districts/cities in North Sulawesi. Data is collected through in-depth interviews, direct observation, and document studies. The data are analyzed thematically, which includes stages of organizing data, reading the entire data set, coding, identifying key themes, and interpreting the data within the framework of transformative Islamic education theory in the political context. Triangulation is used to ensure the validity of the data. The study’s results indicate that transformative Islamic political education by religious figures successfully increased active and responsible political participation and shaped critical political awareness among the Muslim community in North Sulawesi. In addition, the study also found that the Muslim community in North Sulawesi is increasingly aware of the boundaries between religion as a moral guide in politics and religion as a political tool that can be exploited for specific interests. This study has some limitations, such as being limited to the North Sulawesi region, only studying Islamic religious figures, and focusing on the 2024 General Election, which does not yet represent political education outside the election context. Therefore, further research is recommended to expand the regional scope, conduct interfaith studies, and analyze political education by religious figures in a broader socio-political context.